2009
DOI: 10.1016/j.resp.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of chemosensitivity in neurons from the nucleus tractus solitarii (NTS) of neonatal rats

Abstract: We studied the development of chemosensitivity during the neonatal period in rat Nucleus tractus solitarii (NTS) neurons. We determined the percentage of neurons activated by hypercapnia (15% CO2) and assessed the magnitude of the response by calculating the chemosensitivity index (CI). There were no differences in the percentage of neurons that were inhibited (9%) or activated (44.8%) by hypercapnia or in the magnitude of the activated response (CI 164±4.9%) in NTS neurons from neonatal rats of all ages. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…We found that SC neurons from adult rats had a maintained acidification with a lack of pH i recovery in response to HA, which is similar to what has been found in SC neurons from neonates (23,42), and that the percentage of SC neurons activated or inhibited by HA and the magnitude of these responses were unchanged in adult rats compared with neonates (5). This developmental profile did not coincide with previously described patterns for the development of the rat ventilatory response to hypercapnia (6,49).…”
supporting
confidence: 63%
See 4 more Smart Citations
“…We found that SC neurons from adult rats had a maintained acidification with a lack of pH i recovery in response to HA, which is similar to what has been found in SC neurons from neonates (23,42), and that the percentage of SC neurons activated or inhibited by HA and the magnitude of these responses were unchanged in adult rats compared with neonates (5). This developmental profile did not coincide with previously described patterns for the development of the rat ventilatory response to hypercapnia (6,49).…”
supporting
confidence: 63%
“…Synaptic blockade (SNB) solution was modified from aCSF and contained 0.2 mM CaCl 2 and 11.4 mM MgSO 4 ([NaCl] was adjusted to maintain osmotic balance) (5, 7). Carbenoxolone (CARB; 100 M) was added to SNB solution to block electrical transmission (5,9). Isohydric hypercapnic (IH) solution was modified from aCSF with NaHCO 3 Ϫ increased to 77 mM and NaCl decreased to 73 mM to keep pH o and osmotic pressure the same.…”
Section: Solutionsmentioning
confidence: 99%
See 3 more Smart Citations